2022
DOI: 10.2147/idr.s344437
|View full text |Cite
|
Sign up to set email alerts
|

Early Evidence of Circulating SARS-CoV-2 in Unvaccinated and Vaccinated Measles Patients, September 2019–February 2020

Abstract: Background The global emergence of coronavirus disease 2019 (COVID-19) has challenged healthcare and rapidly spread over the globe. Early detection of new infections is crucial in the control of emerging diseases. Evidence of early recorded COVID-19 cases outside China has been documented in various countries. In this study, we aimed to identify the time of SARS-CoV-2 infection circulation by retrospectively analyzing sera of measles patients, weeks before the reported first COVID-19 cases in Ango… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…Our analyses indicated that the first introduction event was inferred during the first months of 2020, and most likely originated from Southern African countries, despite the first reported case being linked to Portugal (Figure 1A). In agreement with previous findings, 29 our analyses indicated that cases may have occurred undetected before the first case was reported. Similar to Brazil and Portugal, the high level of virus introduction and exportation events noted between Angola, Namibia, and South Africa were most likely due to their strong economic ties, particularly in the mining and construction sectors, and many Angolans travel to South Africa and Namibia for business, education, and tourism purposes 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Our analyses indicated that the first introduction event was inferred during the first months of 2020, and most likely originated from Southern African countries, despite the first reported case being linked to Portugal (Figure 1A). In agreement with previous findings, 29 our analyses indicated that cases may have occurred undetected before the first case was reported. Similar to Brazil and Portugal, the high level of virus introduction and exportation events noted between Angola, Namibia, and South Africa were most likely due to their strong economic ties, particularly in the mining and construction sectors, and many Angolans travel to South Africa and Namibia for business, education, and tourism purposes 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Several lines of evidence suggest that SARS-CoV-2 had already been spreading unnoticed for some time prior to being recognized. In fact, SARS-CoV-2 RNA was detected in wastewaters in Northern Italy in late December 2019 ( La Rosa et al, 2021 ) and in Brazil in November 2019 25 , and there is some indirect evidence of 2019 infections through antibody detection in France ( Carrat et al, 2021 ), Italy ( Apolone et al, 2020 ; Montomoli and E, 1401 ), UK ( Ng et al, 2020 ), the USA ( Basavaraju et al, 2021 ), and Angola ( Paixao et al, 2022 ). In addition, SARS-CoV-2 RNA was detected as early as December 2019 in a respiratory sample from a French patient hospitalized for haemoptysis ( Deslandes et al, 2020 ), in the oropharyngeal swab from a child from Milan (Lombardy) with suspected measles ( Amendola et al, 2021 ), and in the blood and lungs of a patients that died in Milan because of acute circulatory insufficiency ( Lai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…To stop the reaction, 100 mL of 1% SDS (sodium dodecyl sulfate) was added. When a cross‐reactive sample showed at least a twofold rise in titer, it was deemed positive; otherwise, the result suggested a potential cross‐reaction between flaviviruses 17,18 …”
Section: Methodsmentioning
confidence: 99%